X-RAYING THE BOUNDS OF THE IGBO APPRENTICESHIP SYSTEM (IAS): IMPLICATIONS FOR ENTREPRENEURSHIP EDUCATION AND JOB CREATION IN EMERGING ECONOMIES - Matthew Agama, Adoga; Cynthia Ohajionu, Uchechi (International Journal of Psychosocial Rehabilitation, 2024)
The overall aim of this study is to provide contextual evidence and deepen understanding of how the Igbo Apprenticeship System, anchored on the Theory of Experiential Learning (TEL), can enhance the effectiveness of entrepreneurship education and practice in Nigeria and other emerging economies. The research design/approach adopted in this study is the Model approach for designing conceptual studies.This approach involves identifying new connections between phenomena, building of theoretical propositions that uncover new constructs and/or connections between constructs, and explaining the reason behind the outcome from a sequence of events.A functional and viable entrepreneurial development system with almost a century-long evidence of job and wealth creation exists to addresscritical macroeconomic issues such as rising unemployment, widespread poverty and economic stagnation. The proposed adapted IAS significantly reduces rate of startup failures, increases rate of business startups and ultimately, facilitates national economic growth and development. These arguments are not simply based on the observable evidence of the socioeconomic impact of the IAS among the Igbo ethnic group, but also on grounded theory of learning (Experiential Learning Theory) and emerging evidences from empirical studies in entrepreneurship education and practice